THE EFFECT OF EXPLOSIVE POWER LEG MUSCLE, FOOT-EYE COORDINATION, REACTION SPEED AND CONFIDENCE IN THE ABILITY OF THE CRESCENT KICK - Padli Arsyad; A Sofyan Hanif; James Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The aim of this study was to determine the effect of leg muscle explosive power, foot-eye coordination, reaction speed and confidence in the ability of the crescent kick. This study uses a survey to look at the relationship between variable. Data analysis techniques using path analysis (path analysis) Path analysis techniques can be used to examine the effect of direct and indirect factors influence explosive power leg muscle, foot-eye coordination, reaction speed and trust themselves on the ability of 30 athletes crescent kick parried Lampung, the provincial government of Lampung, preparation in Porwil Bangka Belitung.Overall it can be concluded that after the test statistics of the empirical data which have been obtained from the field, it can be said that the four independent variables that explosive power leg muscle, coordination ankles, reaction speed and confidence to have a positive influence directly significantly from the ability to kick sickle athletes martial Lampung, the provincial government of Lampung, preparation in Porwil Bangka Belitung. Keywords: explosive power leg muscle, foot-eye coordination, reaction speed and confidence and the ability of the crescent kick